Democracy Growth Activities in Multicultural Students in Girl Junior High School Nawa Kartika of Nahdlotul Ulama - Silahuddin, Muhammad; Suyahmo, Suyahmo; Sunarjan, Y.Y.F.R. (Universitas Negeri Semarang, 2019)
Important values ​​of democracy are nurtured in Indonesia as the diverse community of Indonesia, including Girl Junior High School Nawa Kartika of Nahdlotul Ulama, is a school with students from different regions, ethnic and cultural backgrounds. This study aimed to describe and analyze the growth of democratic values, reactions, effects and barriers to the growth of democratic values ​​in multicultural students at Girl Junior High School Nawa Kartika of Nahdlotul Ulama. This study uses descriptive qualitative explanatory methods, which is to describe the situation and analyze something or what is happening when the research is done with data collection techniques in the form of observations, interviews and documentation, to check the validity of data in qualitative research, then the level of data confidence using triangulation techniques comparing the sources of data obtained. The growth of democratic values ​​in Girl Junior High School Nawa Kartika of Nahdlotul Ulama was carried out through Intra and extracurricular activities. Intramural, such as: Social Sciences, Charter Education and Citizenship, Curriculum Learning 2013, and Class Counseling. Extracurricular activities, such as student council activities, Child Scouts, NU Women's Student Association, and Class meetings. Emerging democratic values ​​include justice, freedom, participation, tolerance, criticism, honesty, respect for diversity and resolving conflicts peacefully and voluntarily. Feeling effects include students being more aware and able to apply the value of democracy to their daily lives in their surroundings.